Synthetic Biology Resources on the Internet. - Dana Antonucci-Durgan (Issues in Science and Technology Librarianship)
Synthetic biology, a branch of biotechnology, uses engineering principles to create new biological entities. In addition to literature on current research projects, researchers need to be aware of the social, ethical and security issues surrounding this science. This guide highlights synthetic biology web resources freely available on the Internet. [ABSTRACT FROM AUTHOR]